2016
DOI: 10.1002/etc.3522
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the physiological and biochemical responses of different tobacco (Nicotiana tabacum) genotypes to lead toxicity

Abstract: In the present study, the effects of lead (Pb) uptake and toxicity were investigated in a hydroponic culture using 7 tobacco (Nicotiana tabacum L.) genotypes (Bina 1 [B1], Kutsaga Mammoth 10 [KM10], Nanjing 3 [N3], Kutsaga 35 [K35], Kutsaga E1 [KE1], Cocker 176 [C176], and Kutsaga RK6 [KRK6]) that differed in Pb tolerance. Lead was applied as a solution of Pb nitrate at concentrations of 0 μM, 10 μM, 250 μM, and 500 μM. After 4 wk of Pb treatment, tissue biomass and photosynthetic parameters were measured and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In-situ localization of Pb ions in roots revealed enhancement in Pb content in response to increment in metal concentration. Similar elevation in Pb content was reported in Oryza sativa 73 , Nicotiana tabaccum 74 , Medicago sativa 75 and Triticum aestivum 76 . The bulk of Pb in soil is absorbed by roots of plants and bind to the carboxyl group of mucilage uronic acids 77 .…”
Section: Discussionsupporting
confidence: 81%
“…In-situ localization of Pb ions in roots revealed enhancement in Pb content in response to increment in metal concentration. Similar elevation in Pb content was reported in Oryza sativa 73 , Nicotiana tabaccum 74 , Medicago sativa 75 and Triticum aestivum 76 . The bulk of Pb in soil is absorbed by roots of plants and bind to the carboxyl group of mucilage uronic acids 77 .…”
Section: Discussionsupporting
confidence: 81%
“…Obviously the addition of Ni and Pb induced a decrease in biomass value with the greatest decrease being noted in the tobacco cultivars after addition of N 1 (NPK+10 mg kg -1 Ni) and P 1 (NPK+10 mg kg -1 Pb) doses. Pb accumulation in plant tissue caused plant stress which affected plant root and shoot growth thereby leading to a reduction in biomass (Maodzeka et al, 2017). With increasing Pb applications, it was observed that there were statistically significant decreases in root and green parts dry matter yields (Kınay and Erdem, 2019).…”
Section: Biomassmentioning
confidence: 99%
“…Tobacco (Nicotiana tabacum L.) is recognized as an effective accumulator of metals from the soil, and can accumulate relatively high concentrations in its organs, mainly leaves (Mench et al, 1989;Doroszewska and Bebec, 2004;Vera-Estrella et al, 2017;Rong et al, 2020). It is reported that tobacco is able to produce high biomass rates, easy to find, can be grown over large areas, and can be accepted as hyper-accumulator for some heavy (Vanlı, 2007;Vamerali et al, 2010;da Silva et al, 2016;Maodzeka et al 2017;Palusińska et al, 2020). The uptake of heavy metal concentrations in tobacco leaves differs widely, and it mainly depends on the tobacco cultivars/genotypes, soil types or conditions, soil organic matter content, pH of the soil, environment and some other factors (Adamu et al, 1989;Wagner et al, 1988 ;Tsadilas et al, 2005;Piano et al, 2008;Golia et al, 2009;Zaprjanova et al, 2010;Regassa and Chandravanshi, 2016;Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco has the potential to accumulate Cd and Pb from contaminated soil [7]. Excessive Cd taken up by tobacco inhibits the absorption of N, P, and K, reducing the biomass of shoot and root [8], while Pb mainly influences seed germination and photosynthesis [9]. In contrast, Cu and Zn, which are essential mineral elements for plant growth, are crucial for maintaining chloroplast structure, enzyme activity, tobacco aroma and growth [10].…”
Section: Introductionmentioning
confidence: 99%